2017
DOI: 10.1001/jamaneurol.2016.5197
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum MicroRNAs and Magnetic Resonance Imaging Measures of Multiple Sclerosis Severity

Abstract: IMPORTANCE MicroRNAs (miRNAs) are promising multiple sclerosis (MS) biomarkers. Establishing the association between miRNAs and magnetic resonance imaging (MRI) measures of disease severity will help define their significance and potential impact. OBJECTIVE To correlate circulating miRNAs in the serum of patients with MS to brain and spinal MRI. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study comparing serum miRNA samples with MRI metrics was conducted at a tertiary MS referral center. Two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 90 publications
5
65
1
1
Order By: Relevance
“…Lesion analysis was carried out in a blinded manner and researchers were not aware of clinical and demographic characteristics. The T2 dual-echo scans were applied to a fully automated pipeline in SPM (v.12; Wellcome Department of Cognitive Neurology, London, UK, http://www.fil.ion.ucl.ac.uk/spm/) to derive maps of GM, WM, and CSF compartments, for the calculation of intracranial volume and brain parenchymal fraction (BPF) [55][56][57] (Fig. 1).…”
Section: Mri Analysis 231 Brain Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion analysis was carried out in a blinded manner and researchers were not aware of clinical and demographic characteristics. The T2 dual-echo scans were applied to a fully automated pipeline in SPM (v.12; Wellcome Department of Cognitive Neurology, London, UK, http://www.fil.ion.ucl.ac.uk/spm/) to derive maps of GM, WM, and CSF compartments, for the calculation of intracranial volume and brain parenchymal fraction (BPF) [55][56][57] (Fig. 1).…”
Section: Mri Analysis 231 Brain Atrophymentioning
confidence: 99%
“…Taken together, these results show the ability of DMTs to exert a partial but significant effect on limiting the rate of cerebral GM atrophy. Numerous mechanisms have been proposed regarding the pathophysiology of GM atrophy in patients with MS, including direct formation of demyelinating plaques, microglial proliferation, leptomeningeal inflammation, anti-lipid antibodies, micro-RNAs, oxidative stress, and Wallerian degeneration [27,44,56,57,[62][63][64][65][66]75]. Understanding fingolimod's proposed mechanism of action may provide some explanation as to how this DMT impacts GM atrophy.…”
Section: Tablementioning
confidence: 99%
“…[21,22] miRNA dysregulation has been reported in various immune cells of patients with MS; some studies have demonstrated changes in miRNA expression in the brain tissue and immune cells of patients with MS and associations between MS progression and miRNA expression. [23,24] Numerous studies have reported a correlation between miR-10a and different autoimmune diseases and T cells, [13,14] revealing that miR-10a is expressed at high levels in naturally occurring Treg cells and that Treg cell miR-10a expression is inversely correlated with susceptibility to autoimmune disease. [13] As mentioned previously, miR-10a probably contributes to other autoimmune diseases via a similar immune pathological mechanism; therefore, we examined the miR-10a targets HDAC4 and HOXA1 are involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple miR‐181 members are downregulated in active and chronic MS lesions and in demyelinated hippocampi (Dutta et al, ). Furthermore, miR‐181c was identified as higher in RRMS than progressive MS patient CSF (Haghikia et al, ), and serum miR‐181c expression is negatively correlated with T1:T2 MRI ratios in MS patients (Regev et al, ). This suggests that miR‐181c is important for protecting myelin or that it is simply a marker for maturing oligodendrocytes.…”
Section: Mirnas As Intrinsic Cues Influencing Remyelinationmentioning
confidence: 99%